GOALS OF ISLAMIC EDUCATION REVISITED: A THEME OF UNITY AND DIVERSITY - Zabihollahi, Kazem (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2025)
This article critically examines the goal(s) of Islamic education, with a particular focus on the interpretations advanced by William Chittick. This examination occurs within the context of the unitary theistic objective intrinsic to Islamic education, contrasting it with the multiplicity of secular goals underpinning Western education. The critique is centred on Chittick’s assertion that modern Western education, dominated by the principle of takthīr—multiplicity—is fundamentally incompatible with the unifying vision of tawhīd—the unity of God—inherent in traditional Islamic education. At the heart of this inquiry lies the question: can the objective(s) of Islamic education, firmly rooted in the principle of tawhīd, as Chittick steadfastly asserts, coexist with the Western educational framework, which is grounded in takthīr? Drawing from classical Islamic thought with a particular focus on Sufism, the paper revisits the triadic structure of knowledge in Islamic intellectual tradition: transmitted, intellectual, and inspired knowledge, which aims to cultivate the soul’s spiritual transformation. While Chittick views tawhīd as the ultimate guiding principle. This paper, through a critical-analytical framework, contends that tawhīd and takthīr are inextricably compatible and interdependent through the lens of waḥda (unity-in-diversity and diversity-in-unity), compelling us to engage with the nuanced interplay between these seemingly opposing forces within the realm of education.